Genocide and settler society : frontier violence and stolen indigenous children in Australian history - Moses, A. Dirk (War and genocide., 2005)
Colonial Genocide has been seen increasingly as a stepping-stone to the European genocides of the twentieth century, yet it remains an under-researched phenomenon. This volume reconstructs instances of Australian genocide and for the first time places them in a global context. Beginning with the arrival of the British in 1788 and extending to the 1960s, the authors identify the moments of radicalization and the escalation of British violence and ethnic engineering aimed at the Indigenous populations, while carefully distinguishing between local massacres, cultural genocide, and genocide its.